Which Relationship Skills Count Most? A Large-Scale Replication. Issue 4 (1st October 2016) - Epstein, Robert; Robertson, Ronald E.; Smith, Rachel; Vasconcellos, Tyler; Lao, Megan
Abstract: In a large-scale follow-up to a recently published study, data obtained from 25, 507 subjects in 58 countries (mainly the United States and Canada) were analyzed in an attempt to rank order seven important relationship competencies. In both studies, two competencies—communication and knowledge of partner—proved to be the strongest predictors of self-reported satisfaction in current relationships, a finding that might help provide some guidance for relationship education and therapy. Although both studies showed little differences overall between the relationship skills of males and females—that is, only small, nonsignificant differences in total scores obtained on the testing instrument—both studies found clear differences in the kinds of skills males and females bring to intimate relationships, a finding that is consistent with the findings of other studies. Effects were also found for race, education, and sexual orientation but not for age or country of residence.